Effect of Nano-encapsulation of Noni (Morinda citrifolia) Fruit Extract on Jejunal Morphology and Microbial Populations in Laying Hens - Choiri, Zainal; Dono, N. Danar; Ariyadi, Bambang; Hanim, Chusnul; Martien, Ronny; Zuprizal (Pakistan Journal of Nutrition, 2017)
Objective: This study aimed to analyze the effect of nano-encapsulation of noni (Morinda citrifolia) fruit extract in drinking water on antibacterial activity and the morphology of intestinal villi in laying hens. Materials and Methods: The experiment was conducted in a completely randomized design consisting of 6 treatments and 5 replicates, with 12 chickens (20 weeks) in each replicate pen. The treatments were: P0 = Water without an additive (negative control), P1 = Water+50 mg/hen of tetracycline (positive control), P2 = Water+0.5% extract of noni fruit, P3 = Water+0.5% nano-encapsulation of noni fruit extract, P4 = Water+1% nano-encapsulation of noni fruit extract and P5 = Water+1.5% nano-encapsulation of noni fruit extract. At the end of the experiment (5 weeks), parameters included bacterial populations in the small intestine (Escherichia coli, Bacillus subtilis and Salmonella sp.) and the morphology of intestinal villi (villus height, villus width, crypt depth and villus height: Crypt depth) were observed. Data were analyzed statistically using one-way ANOVA. Orthogonal contrasts were used to analyze all data with significant differences. Results: The results showed that the addition of 1% nano-encapsulation of noni fruit extract in drinking water did not affect the morphology of the intestinal villi or the populations of Bacillus subtilis and Salmonella sp., but it reduced the population of Escherichia coli (p